The impact of parental income and education on the schooling of children - Arnaud Chevalier; Colm Harmon; Vincent O'Sullivan; Ian Walker (The Economic and Social Research Institute (ESRI), 2013)
We investigate the relationship between early school-leaving and parental education and paternal income using UK Labour Force Survey data. OLS estimation reveals modest effects of income, stronger effects of maternal education relative to paternal, and stronger effects on sons. Using IV methods to simultaneously model the endogeneity of parental education and income, we find no effect of maternal education. Under certain assumptions, paternal education remains significant (for daughters only). Similarly there are modest effects of paternal income for sons. Thus policies that alleviate income constraints to alter schooling decisions may not be as effective as policies which increase permanent income.
Keywords: 330; early school leaving; intergenerational transmission